2017
DOI: 10.1097/j.pain.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 editing of Nf1 gene identifies CRMP2 as a therapeutic target in neurofibromatosis type 1-related pain that is reversed by (S)-Lacosamide

Abstract: Neurofibromatosis type 1 (NF1) is a rare autosomal dominant disease linked to mutations of the Nf1 gene. Patients with NF1 commonly experience severe pain. Studies on mice with Nf1 haploinsufficiency have been instructive in identifying sensitization of ion channels as a possible cause underlying the heightened pain suffered by patients with NF1. However, behavioral assessments of Nf1 mice have led to uncertain conclusions about the potential causal role of Nf1 in pain. We used the clustered regularly interspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 67 publications
3
85
1
Order By: Relevance
“…To investigate the physiological role of the CRMP2-neurofibromin interaction, a CRISPR/Cas9 strategy truncating the C-terminal domain of neurofibromin was adopted and then DRGs from these CRISPR/CAs9-edited rats were electrophysiologically characterized [115]. These recordings demonstrated that CRISPR/Cas9-editing of Nf1 and neurofibromin truncation in rat DRGs resulted in ion channels with biophysical properties essentially parallel to those of Nf1 +/− DRGs; augmented Na + and Ca 2+ currents were observed in addition to hyperexcitability (determined by increased action potential frequency and decreased threshold), while K + currents were not significantly different [112].…”
Section: Dysregulation Of Vgccs In Neuropathic Painmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the physiological role of the CRMP2-neurofibromin interaction, a CRISPR/Cas9 strategy truncating the C-terminal domain of neurofibromin was adopted and then DRGs from these CRISPR/CAs9-edited rats were electrophysiologically characterized [115]. These recordings demonstrated that CRISPR/Cas9-editing of Nf1 and neurofibromin truncation in rat DRGs resulted in ion channels with biophysical properties essentially parallel to those of Nf1 +/− DRGs; augmented Na + and Ca 2+ currents were observed in addition to hyperexcitability (determined by increased action potential frequency and decreased threshold), while K + currents were not significantly different [112].…”
Section: Dysregulation Of Vgccs In Neuropathic Painmentioning
confidence: 99%
“…These recordings demonstrated that CRISPR/Cas9-editing of Nf1 and neurofibromin truncation in rat DRGs resulted in ion channels with biophysical properties essentially parallel to those of Nf1 +/− DRGs; augmented Na + and Ca 2+ currents were observed in addition to hyperexcitability (determined by increased action potential frequency and decreased threshold), while K + currents were not significantly different [112]. In both male and female rats, neurofibromin truncation led to the development of thermal hyperalgesia [115]. …”
Section: Dysregulation Of Vgccs In Neuropathic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Actions of CRMP2 are tightly regulated by post-translational modifications [1]. In chronic neuropathic pain, we found that CRMP2 phosphorylation by cyclin-dependent kinase 5 (Cdk5) on Serine 522 (S522) was sufficient for mechanical allodynia [2] through the facilitation of CaV2.2 and NaV1.7 function [4][5][6][7][8]. By contrast, CRMP2 phosphorylation by the src tyrosineprotein kinase Fyn on tyrosine 32 (Y32) inhibits NaV1.7 [4].…”
mentioning
confidence: 99%